Enhanced compressive strength and in vitro degradation of porous pectin/ calcium phosphate cement scaffolds by freeze casting without sintered - Hao Zhang; Yufei Tang; Xuan Zhou; Qian Liang; Yani Sun; Bo Zhang; Kang Zhao; Zixiang Wu (Journal of Materials Research and Technology, 2025)
The development of biodegradable bone scaffolds that align with the growth cycle of new bone has become a prominent focus in the field of bone defect repair. The sintered porous hydroxyapatite scaffolds exhibit a high degree of crystallization and demonstrate a slow degradation rate following implantation. The apatite phase with low crystallinity can be obtained following the hydration reaction of the non-sintered calcium phosphate bone cement (CPC) scaffolds. However, this leads to the formation of a weak alkaline environment during degradation, ultimately resulting in unsustainable degradation. The present study focuses on the fabrication of porous pectin/CPC composite scaffolds through two approaches during the preparation process of non-sintered porous CPC scaffolds: uniform composite and surface modification. The degradation performance of porous composite scaffolds exhibited an increase with the rise in pectin content. At a pectin content of 70 mg/mL, the scaffolds demonstrated a degradation rate of 13.79% within a span of 30 days. The mechanical properties of the porous scaffolds were enhanced with an increase in pectin concentration through surface coating. When the pectin concentration was 5 wt%, the scaffold exhibited a compressive strength of 8.72 MPa, an elastic modulus of 0.82 GPa, and experienced a degradation rate of 12.57% after a period of 30 days. The local acidic environment not only facilitates the dissolution of bone-like apatite but also enhances cell proliferation and adhesion. Pectin/apatite porous scaffolds exhibit excellent biocompatibility, offering a novel approach for the development of biodegradable bone replacement scaffolds.